Kontribusi Perilaku Kepemimpinan Kepala Sekolah, Iklim Kerja Sekolah, Kepuasan Kerja Guru, dan Komitmen Kerja Guru Terhadap Kinerja Guru CCS Bali - S. Suyanti; I.P.W. Ariawan; D.G.H. Divayana (Jurnal Administrasi Pendidikan Indonesia, 2021)
The purpose of this study was to determine the contribution of principal leadership behavior, school work climate, teacher job satisfaction, and teacher work commitment both individually and collectively on the performance of CCS Bali teachers. This ex-post facto research design involved 40 Indonesian teachers at CCS Bali. The data collection technique is a closed questionnaire containing a series of statements containing five possible answers. Meanwhile, descriptive statistical techniques, simple regression, and multiple regressions were used to analyze the research data. Significant contributions between each variable both individually and collectively were found from the results of the analysis carried out, which included: (1) the principal's leadership behavior contributed significantly to the performance of CCS Bali teachers with a contribution of 0.520 and made an effective contribution 19.34%, (2) the school work climate contributed significantly to the performance of CCS Bali teachers with a contribution of 0.418 and an effective contribution of 8.11%, (3) teacher job satisfaction contributed significantly to the performance of CCS Bali teachers with a contribution of 0.336 and made an effective contribution of 9.27%, (4) the work commitment of teachers contributed significantly to the performance of CCS Bali teachers with a contribution of 0.504 and made an effective contribution of 9.37%, (5) collectively, principal leadership behavior, school work climate, teacher job satisfaction, and teacher work commitment contributed significantly to performance the work of CCS Bali teachers with a contribution of 0.679 and an effective contribution of 46.1%. Based on the results of these studies, the performance of CCS Bali teachers is influenced by the above variables.